Doctor patient relationship: Changing scenario in India (Asian Journal of Medical Sciences, 2016)
God has chosen special persons to take care of the physical pains and sufferings of man and such persons are known as doctors. But recently countrywide dissatisfaction on the major pillar of the medical services raises number of questions. In this present article authors have tried to find out the related factors with the changing scenario of doctor- patients relationship from India’s prospective. In the ancient India, doctors were enjoying the highest level of respect in the society because of the attitude and activity towards the patient. In the last decade of the 20th century and beginning of 21st century, a chronic dissatisfaction began to settle over the relationships between doctors and patients. High level of corruption in the health care industry, inequity in health care delivery, technological development in medical science, growth of health insurance, patient’s desire in share decision making, information technology development are few factors behind changing doctor- patient relationship. If physicians take a little more time in reassuring patients in the old fashioned way, this will restore the deteriorating relationship.Asian Journal of Medical Sciences Vol.7(4) 2016 1-5